2012
DOI: 10.1152/ajprenal.00656.2011
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of circulating and renal ACE2 and ACE in hypertensive mRen2.Lewis rats with early-onset diabetes

Abstract: Yamaleyeva LM, Gilliam-Davis S, Almeida I, Brosnihan KB, Lindsey SH, Chappell MC. Differential regulation of circulating and renal ACE2 and ACE in hypertensive mRen2.Lewis rats with early-onset diabetes. Am J Physiol Renal Physiol 302: F1374 -F1384, 2012. First published February 29, 2012 doi:10.1152/ajprenal.00656.2011We examined the impact of early diabetes on the circulating and kidney renin-angiotensin system (RAS) in male and female mRen2.Lewis (mRen2) hypertensive rats. Diabetes (DB) was induced by stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
85
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(94 citation statements)
references
References 65 publications
8
85
1
Order By: Relevance
“…These results are in concordance with studies by Choi et al (9) who used an experimental unilateral ureteral obstruction mouse model. The increase in serum ACE2 activity in diabetes has been previously published (33,44,47,49). However, our study describes the effects of paricalcitol on ACE2 activity.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…These results are in concordance with studies by Choi et al (9) who used an experimental unilateral ureteral obstruction mouse model. The increase in serum ACE2 activity in diabetes has been previously published (33,44,47,49). However, our study describes the effects of paricalcitol on ACE2 activity.…”
Section: Discussionmentioning
confidence: 72%
“…ACE2 activity has been shown to be altered in diabetic kidney disease, hypertensive renal disease, and various models of kidney injury (3,40,49,50). Our group has recently demonstrated that circulating and renal ACE2 is increased in NOD mice, and that enzyme expression was lowered by insulin treatment (33).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, microliter amounts of serum or microgram quantities of tissue are required with this approach. We find that circulating ACE and ACE2 activities were significantly increased in a model of diabetic hypertension; however, ACE activity remained far higher than ACE2 which may contribute to the greater content of ANG II in diabetic mRen2.Lewis rats (148). Kinetic analysis using both labeled and unlabeled ANG II confirmed a sevenfold increase in the V max value for serum ACE2 in the female diabetic rat (148).…”
Section: Ras Protein Componentsmentioning
confidence: 64%
“…ACE2 is a membrane-bound monocarboxypeptidase (120 kDa) that converts ANG II directly to ANG-(1-7). Circulating levels of ACE2 are typically quite low particularly compared with ACE; however, serum ACE2 activity is elevated in diabetes, heart failure, and hypertension (41,136,148). ACE2 has a potentially significant role in the RAS pathway as a single catalytic step degrades ANG II but activates the ANG-(1-7) axis ( Fig.…”
Section: Ras Protein Componentsmentioning
confidence: 99%
See 1 more Smart Citation